2007
DOI: 10.1063/1.2768201
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism in nanoscale BiFeO3

Abstract: A remarkably high saturation magnetization of ~0.4mu_B/Fe along with room temperature ferromagnetic hysteresis loop has been observed in nanoscale (4-40 nm) multiferroic BiFeO_3 which in bulk form exhibits weak magnetization (~0.02mu_B/Fe) and an antiferromagnetic order. The magnetic hysteresis loops, however, exhibit exchange bias as well as vertical asymmetry which could be because of spin pinning at the boundaries between ferromagnetic and antiferromagnetic domains. Interestingly, like in bulk BiFeO_3, both… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
163
4
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(185 citation statements)
references
References 16 publications
17
163
4
1
Order By: Relevance
“…26,16 The improvement in magnetization in nanoscale particle may be due to the suppression of helical order and increase in spin canting due to the lattice strain, which gives rise to weak ferromagnetism. 27 The observed weak ferromagnetism may also be attributed to the structural distortions of BFO by incorporation of PbTiO 3 . Incorporation of Pb 2+ cation at Bi 3+ sites and Ti 4+ at Fe 3+ site causes the canted spin arrangement of unpaired electron on Fe 3+ ions according to the DMI.…”
mentioning
confidence: 99%
“…26,16 The improvement in magnetization in nanoscale particle may be due to the suppression of helical order and increase in spin canting due to the lattice strain, which gives rise to weak ferromagnetism. 27 The observed weak ferromagnetism may also be attributed to the structural distortions of BFO by incorporation of PbTiO 3 . Incorporation of Pb 2+ cation at Bi 3+ sites and Ti 4+ at Fe 3+ site causes the canted spin arrangement of unpaired electron on Fe 3+ ions according to the DMI.…”
mentioning
confidence: 99%
“…It has also been reported that BiFeO 3 nanoparticles smaller than ~ 92 nm in size show an enhancement in magnetization strongly dependent on the particle size [158][159][160][161]. This improvement in magnetization has been related with the frustration of anti-ferromagnetism in reduced size particles as well as with the presence of decompensate spins and anisotropic stresses in the surface of the nanoparticles [159].…”
Section: Magnetic Response In Bifeo 3 Materialsmentioning
confidence: 97%
“…64 nm, show an antiferromagnetic behavior. However, this superstructure can be frustrated leading to a ferrimagnetic response, something which has been pursued by different strategies: applying high magnetic fields (~ 20 T), reducing the particle size, introducing restrictions in thin films or by chemical substitution [2,157,158].…”
Section: Magnetic Response In Bifeo 3 Materialsmentioning
confidence: 99%
“…За счет деформации структуры пленки удается увеличить намагниченность до 8.30 emu/g, в то время как максимальное значение намагниченности для недеформированных пленок колеб-лется от 0.03 до 0.17 emu/g [10,11]. Уменьшение разме-ров нанокристаллов ниже 30 nm, сопровождаемое увели-чением доли поверхности, также приводит к увеличению намагниченности, вызванному искажениями кристалли-ческой решетки и уменьшением отношения c/a [12,13]. Подобные изменения c/a наблюдаются и при замещении ионов Bi 3+ и Fe 3+ , что позволяет рассматривать процес-сы замещения как эффект " химического давления" [14].…”
Section: Introductionunclassified